Performance of Nile tilapia juvenile fed diet containing different dosages ofrecombinant common carpgrowth hormone - Hardiantho, Dian; Alimuddin, .; Prasetiyo, Arief Eko; Yanti, Dwi Hany; Sumantadinata, Komar (Jurnal Akuakultur Indonesia, 2012)
The studywas conductedtodetermine thedose of recombinant common carp growth hormone (rCcGH) supplemented in the commercial diet that generates the best performanceonbodyweight, biomass, andfeed conversion rate of juvenile tilapia.The dose of rCcGH administered was10, 20, and30mg/kg of commercial feed, andnorGH supplementation as control. Eachtreatment was designed in triplicates. Juveniles at average bodylengthof about2cm(average body weight of 0.7 g) were reared in a density of25fish/m2, for three weeks in hapa net at a size of 2×2×1 m3. Fish were fed diet containing rCcGH twicea week with an interval ofthreedays. The juvenile were fed with the rCcGH supplemented diet three times daily at satiation. The results showedthat average body weight andbiomass of fish treated by rCcGH with the doses of 20 and 30 mg/kg feed was higher (p<0.05) than that of 10 mg/kg and control. In addition, feed conversionrate of 20 and 30 mg/kg feed treatments was lower (p<0.05) than that of 10 mg/kg and control. RT-PCR analysisshowedthat expression level of IGF-1 gene in juvenile liver was increased in parallel with the increasing of rCcGH dosages supplemented in diet.This suggestedthatIGF-1 plays an important rolein the induction ofgrowth,andfeed conversionefficiencyof tilapiafed diet containing rCcGH. The bestperformance of juvenile can be obtainedby feeding with diet containingrCcGH20‒30mg/kgof feed. Keywords: rCcGH, IGF-I, recombinant growthhormone,performance, Nile tilapia.